Analisis penerapan standar akuntansi keuangan Entitas tanpa akuntabilitas publik (SAK-ETAP) pada penyajian laporan keuangan BUM Desa (Studi Kasus pada BUM Desa Kerto Raharjo di Desa Sanan Kerto Kec. Turen Kab. Malang) - Angela Astika Udur Sirait; Ana Sopanah; Indah Dewi Nurhayati (Proceeding of National Conference on Accounting & Finance, 2020)
The financial statements are information that presents the financial position and financial perfomance of an entity. The entity can present financial statements with accounting standards. SAK ETAP is an accounting standard used as guidance in the preparation of financial statement for entities that do not have public accountability. This study aims to determine the application of SAK ETAP in preparing financial statements of BUM Desa Kerto Raharjo in desa Sanankerto Kecamatan Turen Kabupaten Malang. The object of this research was conducted at BUM Desa Kerto Raharjo. The focus of this research is to analyze the application of SAK ETAP in BUM Desa Kerto Raharjo financial statements for the peroid 2018. This study uses a descriptive qualitative research method through a case study approach. Data collection techniques through interviews, observation and documentation. Based on the results of data analysis, that the record-keeping (journal) on others transaction and presentation of financial statements carried out by BUM Desa Kerto Raharjo it was not yet appropriate with SAK ETAP. Recording transactions using a daily cash journal by recording cash in and cash out. BUM Desa Kerto Raharjo presenting financial statement only two kinds such us balance sheet and income statement while according to SAK ETAP there are five kinds such us balance sheet, income statement, report of changes in equity, cash flow statement and  notes to financial statement. This is due to the lack of understanding by management regarding SAK ETAP.